(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article considers the necessity of treating metacommunication as a communicative category due to the following its structural components: content plan (stages of nomination and creation of the semantic field of the category), expression plan, which allows to represent a speech situation in the oral or written form, and translation plan, which has no clearly defined structure, but allows to identify different levels of language means marking metacommunicative situations.